Technical regulations as an aggravating circumstance of negligent crimes in the road traffic - Yon Ruesta, Róger (2015)
Driving a car or another vehicle involves a risk per se, but it is allowed since it is a necessary activity for society. However, the risk remains. That is the reason for demanding from drivers a duty of care. Nevertheless, how far should this duty go?In the present article, the author analyzes the precedent in negligent crimes in the road traffic.The author emphasizes that it is necessary to apply technical regulations, also taking into account other factors that may cause the risk, and not limiting the reasoning to understand that the drivers are the only guilty participants.